Resilience, women victims of gender violence and their influence among them, in ages 25 to 50 in the city of Manta. - ÁLVAREZ-SANTANA, CARMITA (2021)
The following work analyzes the way in which resilience influences as a positive learning process in women victims of gender violence, between ages of 25-50 in the city of Manta. This inquiry is of a quantitative-qualitative character of an interpretative type, for data collection, surveys were applied to a total of 383 women in Manta city between the ages of 25-50. The obtained results related to resilience prove that, 85.1% of the surveyed population considers that resilience empowers women victims of gender violence, only 14.9% indicated that they disagree in consequence the inquiry affirm that resilience is definitive in learning and overcoming process of traumatic events in women victims of gender violence.